(untitled) (American Journal of Life Science and Innovation, 2024)
Retroperitoneal cysts of Müllerian origin are rare and often discovered incidentally during surgical procedures or imaging studies. We present a case of a retroperitoneal cyst found during a total laparoscopic hysterectomy performed for myoma removal. A 40-year-old female presented with symptomatic myomas and underwent pre-operative evaluation, including pelvic ultrasound, which revealed no abnormalities apart from the myomas. A cyst was incidentally discovered in the retroperitoneal space during a total laparoscopic hysterectomy procedure. The cyst was excised and sent for histological examination, which confirmed its Müllerian origin. Retroperitoneal cysts of Müllerian origin are rare findings during TLH. This case report highlights the importance of thorough pre-operative evaluation and imaging studies and the significance of intraoperative awareness in identifying incidental findings. Further research is warranted to determine the optimal diagnostic imaging strategies for such cysts.